Netflix Disrupting Dubbing: English Dubs and British Accents - Hayes, Lydia (Journal of Audiovisual Translation, 2021)
In 2017, English dubbing entered the mainstream on the initiative of the subscription video-on-demand service (SVoD) Netflix. Recent English dubs have taken advantage of the largely convention-free English dubbing industry and, in 2019, dubs outsourced by Netflix to VSI London saw the introduction of linguistic variation into the dubs of Spanish originals, such as Alta Mar (High Seas) (Campos and Neira 2019–) and, most notably, Hache (Torregrossa and Trullols 2019–). In these series, a myriad of British accents is used for characterisation as an alternative to standardisation strategies that conflate cultural identities into one, which are prevalent in many consolidated dubbing industries. In addition to the lack of industry precedents and an argued associated malleability of viewers, the diegetic quality of dubbed dialogue seems to have allowed the implausibility of linguistic variation to be accepted by viewers in an extended “suspension of linguistic disbelief” (Romero-Fresco 2009: 49). In this paper, I explore accents as “unit[s] of cultural transmission” aka “memes” (Dawkins 1976: 206), and the specific sets of connotations associated with accents i.e. dialectal memes that are evoked in the original and dubbed versions of the aforementioned series. Emerging norms in UK dubs of Spanish originals are then elucidated. Lay summary For over sixty years now, subtitling has been the default form of translation when bringing foreign films into English-speaking countries. However, Netflix has recently disrupted this practice by providing the alternative option of watching many of its non-English films and series dubbed into English, i.e. the voices of the original actors are replaced with those of voice actors who perform in English instead of, say, Spanish. In many countries where dubbing has long been the default translation practice, such as Spain, the accents used in original versions to create different character identities are dubbed into one standardised Spanish accent, which makes it difficult to distinguish between characters’ social class, among other qualities attached to accent. In the English dubs on Netflix, however, accents are being used for characterisation. In this article, I analyse the use of British accents in Netflix’ dubs of the Spanish-original series Hache and Alta Mar (High Seas), and compare character identities in the original and dubbed versions, according to the cultural connotations triggered by the different accents used in each. I apply theories from the Translation Studies discipline to help understand and support the use of accents in English dubs, as a valid alternative to standardisation strategies in dubbing. Given a significant amount of Netflix’ foreign products are in Spanish, the analysis in this article can be used in future to track changes in English dubs generally and especially English dubs of Spanish-language originals on Netflix, which might use different strategies to English dubs of Danish products, or Spanish products on other streaming platforms, for example.